HTRA1-Related Cerebral Small Vessel Disease: A Review of the Literature - Uemura, Masahiro; Nozaki, Hiroaki; Kato, Taisuke; Koyama, Akihide; Sakai, Naoko; Ando, Shoichiro; Kanazawa, Masato; Hishikawa, Nozomi; Nishimoto, Yoshinori; Polavarapu, Kiran; Nalini, Atchayaram; Hanazono, Akira; et al. (Frontiers in Neurology, 2020)
Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is clinically characterized by early-onset dementia, stroke, spondylosis deformans, and alopecia. In CARASIL cases, brain magnetic resonance imaging reveals severe white matter hyperintensities (WMHs), lacunar infarctions, and microbleeds. CARASIL is caused by a homozygous mutation in high-temperature requirement A serine peptidase 1 (HTRA1). Recently, it was reported that several heterozygous mutations in HTRA1 also cause cerebral small vessel disease (CSVD). Although patients with heterozygous HTRA1-related CSVD (symptomatic carriers) are reported to have a milder form of CARASIL, little is known about the clinical and genetic differences between the two diseases. Given this gap in the literature, we collected clinical information on HTRA1-related CSVD from a review of the literature to help clarify the differences between symptomatic carriers and CARASIL and the features of both diseases. Forty-six symptomatic carriers and 28 patients with CARASIL were investigated. Twenty-eight mutations in symptomatic carriers and 22 mutations in CARASIL were identified. Missense mutations in symptomatic carriers are more frequently identified in the linker or loop 3 (L3)/loop D (LD) domains, which are critical sites in activating protease activity. The ages at onset of neurological symptoms/signs were significantly higher in symptomatic carriers than in CARASIL, and the frequency of characteristic extraneurological findings and confluent WMHs were significantly higher in CARASIL than in symptomatic carriers. As previously reported, heterozygous HTRA1-related CSVD has a milder clinical presentation of CARASIL. It seems that haploinsufficiency can cause CSVD among symptomatic carriers according to the several patients with heterozygous nonsense/frameshift mutations. However, the differing locations of mutations found in the two diseases indicate that distinct molecular mechanisms influence the development of CSVD in patients with HTRA1-related CSVD. These findings further support continued careful examination of the pathogenicity of mutations located outside the linker or LD/L3 domain in symptomatic carriers.